Efficacy of barrier wound protection (using wound protector/retractor[Alexis]) in the prevention of surgical site infections in open abdominal surgeries - Zulpi, Prashant K; Rao, P Rajshekhar (International Journal of Health and Clinical Research, 2021)
Background :Surgical site Infections (SSI) remains an important complication, only secondary to urinary tract infections as the common nosocomial infection in hospitalized patients. This leads to prolonged convalescence, physical and financial burden to patient and hospitals.Alexis wound protector/retractor is identified as a dual role retraction device that also may result in reduced enteric bacterial colonization of the surgical incision site during gastrointestinal surgery. The goal of this study was to evaluate the effectiveness of Alexis wound retractor in prevention of surgical site infections .Methods:Randomized Prospective study of 60 patients undergoing laparotomy/laparoscopic assisted surgeries, divided into two groups, one group using wound protector and the other group without using wound protector, and study the outcome in terms of post surgical incisional wound infection in both groups.Results : Use of Alexis wound retractor reduced the rate of surgical site infections across all sub groups considered . Statistically significant difference in the two arms of this study was found in wound infection rate in patients undergoing surgery for malignant conditions . Marked reduction in surgical site infection was also found in surgeries lasting for less than 180 minutes( no infections in the Alexis group ) , in obese patients ( 14 % vs. 44 %{ Alexis vs conventional group} , p value = 0.07 ) , in emergency surgeries ( no infections in the Alexis group).Conclusion :Use of Alexis wound retractors reduces surgical site infection in laparotomy wounds and requires further evaluation for its application as a means of reducing surgical site infections.